THE USE OF COOP – DIS – Q STRATEGY IN TEACHING READING ANALYTICAL EXPOSITION TO THE ELEVENTH GRADERS OF SMA NEGERI 1 TELUK GELAM - Herbet Spencer (Language and Education Journal, 2018)
The main objective of the study was to find out whether or not there was a significant difference between the students’ reading comprehension achievement who were taught by using Coop-Dis-Q strategy and that of those who were not. This study conducted at SMA Negeri 1 Teluk Gelam which consisted of 168 eleventh-grade students. The sample of the study was 66 students taken by purposive sampling. The data gathered using multiple choice items. Quasi-experimental method was used in this study. The data analyzed by using t-test. The calculation of t-test showed that t-obtained (3.544) was higher than t-table (1.9977). In other words, the null hypothesis (Ho) was rejected and consequently, the alternative hypothesis (Ha) was accepted. It could be stated that there was a significant difference between the students’ reading comprehension achievement who were taught by using story impression strategy and that of those who were not. Coop-Dis-Q strategy made students had an opportunity to work together in comprehending the texts, lead the students to help each other in comprehending the text and kind of questions that were prepared in this strategy and were used to increase students’ reading comprehension. As a result, they could involve actively in reading activity